(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2015)
Physico-chemical properties and mineral contents of tropical fruits available at local market in Dhaka city were evaluated as fruits are the essential part of human diet to supply required micronutrient. Among the analyzed fruits, maximum and minimum amount of moisture was found in java apple (93.26±1.77%) and indian plum (66.86±1.81%) respectively. Mango contains highest amount of total soluble solids (15.20±0.81%) and total sugar (4.71±0.08%). Highest and lowest amount of vitamin C was found in guava (212.82±6.92 mg/100g) and java apple (10±1.77 mg/100g) respectively. Approximate energy value was found highest in indian plum (128.1±5.51kcal/100g) and lowest in green palmyra palm (27.7±2.64 kcal/100g). Indian plum (139.32±9.53mg/100g) and mango (34.03±6.81mg/100g) contain highest and lowest amount of sodium whereas rose apple (75.15±0.02mg/100g) and mango (10.23±1.94mg/100g) contain highest and lowest amount of potassium respectively. Heavy metals (As, Cd, Pb and Hg) were not detected in analyzed tropical fruits. This study suggests that the tropical fruits are enriched in micronutrients. DOI: http://dx.doi.org/10.3329/bjsir.v49i3.22126 Bangladesh J. Sci. Ind. Res. 49(3), 131-136, 2014